2003
DOI: 10.1590/s1984-63982003000200001
|View full text |Cite
|
Sign up to set email alerts
|

A usabilidade e a elaboração de materiais para o ensino de inglês mediado por computador

Abstract: Este trabalho apresenta implicações para a preparação de materiais para o ensino mediado por computador, constatadas através de uma pesquisa na qual um teste de usabilidade foi aplicado a uma atividade de compreensão textual em inglês como LE. O conceito de usabilidade foi dividido em usabilidade de design -com foco na superfície do material -e usabilidade pedagógica -concentrada na apresentação de feedback e de estratégias de leitura. Cinco alunos iniciantes de inglês leram um texto e responderam a perguntas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…The author alleges that the pedagogical usability is more restricted compared with the proposed activity, and that the educational materials shall be developed according to the student. It is observed that the emphasis needs to be on what deals with the pedagogical preparation, so that all actions shall point to the main purpose, whereas a low pedagogical usability affect the learning processes (VETROMILLE- CASTRO, 2003). An author observation is that the pedagogical usability is consolidated through the feedback provided to the student, considering the importance of the moment and the kind of activity proposed, among other pedagogical aspects that constitute this bias.…”
Section: Pedagogical Usabilitymentioning
confidence: 99%
“…The author alleges that the pedagogical usability is more restricted compared with the proposed activity, and that the educational materials shall be developed according to the student. It is observed that the emphasis needs to be on what deals with the pedagogical preparation, so that all actions shall point to the main purpose, whereas a low pedagogical usability affect the learning processes (VETROMILLE- CASTRO, 2003). An author observation is that the pedagogical usability is consolidated through the feedback provided to the student, considering the importance of the moment and the kind of activity proposed, among other pedagogical aspects that constitute this bias.…”
Section: Pedagogical Usabilitymentioning
confidence: 99%
“…Thus, a LO that has granularity that permits reusability and interoperability (these characteristics will be approached next) in the use of the resource at a level that is relevant to the learning process can be considered as having adequate granularity. In other words, the reusability and interoperability of a LO for language learning, from a pedagogical perspective, will fundamentally attend to the principles of CLT (Canale & Swain, 1980;Ellis, 1999Ellis, , 2005 and pedagogical and design usability (Vetromille-Castro, 2003) without ignoring adequate technical principles. The importance of acquiring these new teaching skills as well as the comprehension of how technical aspects can influence learning/teaching had already been mentioned in 2005, by Hampel & Stickler in Compton (2009, p. 73):…”
Section: Defining Learning Objects and Language Learning Objectsmentioning
confidence: 99%
“…We argue that it will be necessary for the development of these objects to be grounded theoretically in their pedagogical aspect. Furthermore, they will have to contemplate the principles of Pedagogical Usability (PU) and Design Usability (DU) (Vetromille-Castro, 2003), which are going to be discussed in the next section.…”
Section: Defining Learning Objects and Language Learning Objectsmentioning
confidence: 99%
See 2 more Smart Citations